Successful pregnancy in a woman with Herlyn-Werner-Wunderlich syndrome: A case report and literature review - Anas R. Tuqan; Rayan R. Salahaldin; Mais E. Abubaker; Basel A. Zaben; Anas M. Barabrah; Mohammad H. Rayyan; Saadeh S. Jaber (Elsevier, 2024)
Herlyn-Werner-Wunderlich (HWW) syndrome is a rare congenital condition characterized by renal agenesis, uterine didelphys, and obstructed hemivagina. This report presents the case of a 19-year-old woman who reported lower abdominal pain and offensive vaginal discharge. Imaging revealed a didelphys uterus, two vaginas, two cervixes, hematocolpos, and an absent right kidney. Surgical intervention involved draining the hematocolpos and excising the uterine septum. After surgery, the patient successfully conceived and had a full-term pregnancy, delivering via cesarean section without complications. This case highlights the importance of early diagnosis and surgical management in preventing complications such as endometriosis and infertility. Prompt recognition and treatment are crucial for preserving fertility in patients with HWW syndrome.